Management of Acute Nonvariceal Upper Gastrointestinal Hemorrhage: Comparison of an American and a Canadian Medical Centre - Laura E Targownik; Ian M Gralnek; Gareth S Dulai; Brennan MR Spiegel; Tommy Oei; Charles N Bernstein (Canadian Journal of Gastroenterology)
OBJECTIVES: Acute nonvariceal upper gastrointestinal hemorrhage (UGIH) remains a common indication for hospital admission. Differences in the structure, process and outcomes of care in the management of acute nonvariceal UGIH between providers in Canada and the United States have not been previously characterized. The aim of the present study was to compare the structure, process and outcomes of care between a Canadian and an American tertiary care medical centre in the management of acute nonvariceal UGIH.